Surgical versus transcatheter mitral valve replacement in functional mitral valve regurgitation - Scott, Erik J.; Rotar, Evan P.; Charles, Eric J.; Lim, D. Scott; Ailawadi, Gorav (Annals of Cardiothoracic Surgery, 2021)
Surgical mitral valve intervention for severe functional, or secondary mitral regurgitation is a viable option for patients deemed to be operative candidates and can be performed via traditional sternotomy or by minimally invasive techniques with similar outcomes. Transcatheter mitral valve replacement is an emerging technology with a potential role in the treatment of functional mitral valve regurgitation. A plethora of devices are currently in development and in various stages of clinical investigation. Operative approach to transcatheter mitral valve replacement varies from a percutaneous transseptal approach to a hybrid percutaneous/surgical apical approach. The Tendyne, Intrepid and Evoque systems show promising results from their early feasibility studies in treatment of patients with mitral regurgitation that were too high risk for surgery. In this review, we describe considerations for surgical and transcatheter mitral valve replacement for functional mitral valve regurgitation.